Pencegahan Perilaku Merokok Remaja Melalui Penyuluhan Bahaya Rokok Elektrik dan Konvensional - Ika Setya Purwanti; Ni Luh Putu Devhy; Diah Prihatiningsih; Ni Wayan Desi Bintari; A.A Gde Oka Widana (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this community service activity is to increase knowledge and understanding of the dangers of smoking for adolescents. Activities are carried out online using the Zoom Meeting application in June 2021. The method of activity by providing socialization of the dangers of smoking to adolescents. The community service participants are 8th grade junior high school students, totaling 64 children. Based on gender, the service participants consisted of 34 male students (53,13%) and 30 female students (46,87%). Based on pre-test, 40,5% of students did not know the dangers of smoking and 59,5% of students knew the dangers of smoking. Based on the results of the post test, it was found that there was an increase in knowledge about the dangers of smoking. As many as 98% know about the dangers of smoking and 2% are less aware of the dangers of smoking. Counselling related to the dangers of smoking can increase adolescent awareness of the magnitude of the adverse effects of smoking on health.